2018
DOI: 10.1128/mra.01003-18
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Avian Coronavirus Strain D274

Abstract: Avian coronavirus, the causative agent of avian infectious bronchitis, occurs as multiple genotypes and lineages, and full genomes are not available for the majority of them. This paper reports the (previously unknown) complete genome sequence of strain D274 of this virus (27,599 nucleotides), isolated from chickens in The Netherlands in 1979.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…More recently, genetic studies have suggested recombination events of circulating IBV in Peru and Uruguay, which might reveal the underlying events of viral evolution occurring in South American countries [ 11 , 12 ]. Furthermore, IBV GI-1 lineage has been detected in countries, such as Brazil [ 13 , 14 , 15 , 16 ], Argentina [ 9 ], Chile [ 17 , 18 ], and Colombia [ 19 ]. Although its first detection in South America dated back to 1950s [ 20 ], it is possible that circulating GI-1 viruses arose from vaccine strains [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, genetic studies have suggested recombination events of circulating IBV in Peru and Uruguay, which might reveal the underlying events of viral evolution occurring in South American countries [ 11 , 12 ]. Furthermore, IBV GI-1 lineage has been detected in countries, such as Brazil [ 13 , 14 , 15 , 16 ], Argentina [ 9 ], Chile [ 17 , 18 ], and Colombia [ 19 ]. Although its first detection in South America dated back to 1950s [ 20 ], it is possible that circulating GI-1 viruses arose from vaccine strains [ 9 ].…”
Section: Introductionmentioning
confidence: 99%